Macroeconomic Determinants of the Jakarta Composite Index: An Arbitrage Pricing Theory Approach - Latifatun Istiqomah; Naufal Noor Hanan (Journal of Business, Finance, and Banking, 2026)
This study aimed to analyze the effect of macroeconomic variables, specifically the exchange rate, inflation, and interest rate (BI Rate), on the Composite Stock Price Index (IHSG) in Indonesia. The research used a quantitative approach with monthly time-series data spanning from January 2021 to December 2025, totaling 60 observations. The data were analyzed using multiple linear regression with Log-Log and Log-Lin specifications through EViews 13 software. To overcome classical assumption violations, specifically heteroskedasticity and positive autocorrelation, the study applied the Heteroskedasticity and Autocorrelation Consistent (HAC) Newey-West standard errors correction. The results of the simultaneous test showed that the exchange rate, inflation, and interest rate significantly influenced the IHSG, which supported the Arbitrage Pricing Theory (APT). However, the partial test revealed an anomaly where the depreciation of the Rupiah exchange rate had a significant positive effect on the IHSG. This finding suggests the presence of a cushioning effect, driven by the windfall profits of export-oriented commodity companies. Meanwhile, inflation and interest rates did not have a significant effect on the IHSG, indicating that the moderate inflation rate and the central bank's hawkish monetary policy were well-anticipated (priced-in) by market investors